Intervensi Masalah Kesehatan ISPA melalui Program BERDIKARI di Dusun Cimanggu Kota Banjar - Salsabila, Analisa; Oktaviani, Ersya Sri; Sugiandika, Tri Retno; Asyi Zamilah, Apipah Rohadatul; Surya Hazani, Dinar Ayu; Zahirah, Ghefira; Aulia, Mediana; Nicholas, Kevin; Rahmawati, Anita; Komalasari, Rini; Amalia, Reva; Saphira, Alma Aulia; Lina, Nur (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Health problems, especially Acute Respiratory Infections (ARI), are still a challenge in Indonesia. The high rate of ARI in Cimanggu Hamlet is caused by the habit of burning waste that pollutes the air. This community service programs aims to increase community awareness about waste management through the BERDIKARI program (Empowering Residents to Manage Waste Independently). The methods used include advocacy, socialization, training, and waste sorting assistance. The evaluation results showed an increase in community knowledge from the pre-test average score of 8,65 to 9,26 in the post-test. This increase indicates the effectiveness of the program in encouraging active participation of the community to manage waste and prevent ARI. These results are important for the sustainability of public health and a cleaner environment.